Desenvolvimento e verificação de propriedades psicométricas de inventário de rastreamento de dificuldades cognitivas (IRDC) em crianças de 6 a 11 anos. - Marino, Regina Luísa de Freitas (2020)
The most frequent complaints from children referred to health professionals such as the psychologist are related to one of the following problems: academic difficulties, attentional impairments or developmental delay. The aim was to develop an inventory that evaluates cognitive functions of children between 6 to 11 years old to track cognitive profiles compatible with Intellectual Disability (mild), Attention Deficit Hyperactivity Disorder and Specific Learning Disorder (dyslexia) to assist in differential diagnosis between these three disorders, since symptoms often overlap. The inventory has two versions: one for child's parents and another for teacher, which can be used in screening sessions or as a comprehensive child assessment as another source of information. In study 1 (identification of the relevant constructs, operational definition of the constructs and development of items), data were collected from three sources of information: parents of children diagnosed with one of the three disorders and professionals who serve this population; search on articles from literature on cognitive profiles of the three disorders, verification of screening instruments for the three disorders and identification of cognitive impairments underlying each diagnostic criterion by the DSM-5. In study 2, an analysis of judges with professionals who serve children with the disorders was carried out, as well as a verification of the items' clarity by the target population (parents and teachers); In study 3, we looked for evidence of validity and precision indicators of the inventory; and in study 4, the level of sensitivity and specificity of the inventory scales was verified. For testing the items performed in studies 3 and 4, data collection was performed with 272 parents and 178 teachers of children between 6 and 11 years old. As for the diagnosis, only 72 children were diagnosed with one of the three disorders and 207 had no suspect of neurodevelopmental disorders. Due to the sample size, for the teacher’s version it was not possible to extract factors and no underlying model was converged. For the parent version, the four-factor solution was the most appropriate, with the following Scales: Attention, Executive Functions, Intelligence and Oral Language. The final version for parents was composed of 60 items, with excellent internal consistency indices (coefficients> 0.90). Finally, ROC curves were performed to verify the sensitivity and specificity of the scales for each disorder. For Intellectual Disability, there was a significant difference between the performance of groups for all scales in the inventory, with higher specificity level for intelligence scale and better sensitivity to written language scale. For ADHD, the scores would significantly differ from H0, that is, they differentiated the groups, only for the Executive Functions and Attention scales. Finally, for Dyslexia, H0 was rejected only on the “Written Language” scale and is therefore the only scale that discriminated between children with dyslexia and typically developing children. In the future, it is necessary to expand the sample size of children diagnosed with one of the three disorders so that new analyzes can be performed and the results can be generalizable to the population.